Quickly and efficiently remove multiple pesticides in tea infusions by low-cost carbonized bacterial cellulose. (1st May 2022) - Zhang, Bingjie; Yu, Jingyang; Li, Changsheng; Wang, Jianli; Zhu, Jianhui; Ma, Yongqiang; Yu, Chunxin; Duan, Liusheng
Graphical abstract: Highlights: CBC were prepared by direct calcination of BC under different temperatures. CBC-350 can remove multiple pesticides in tea infusions quickly and efficiently. The CBC-350 also has excellent adsorption capacity compared to other adsorbents and can be reused at least five times. Abstract: Soaking tea leaves make tea consumers exposure to pesticide residues more easily. However, there are few studies on the removal of pesticides in tea infusions. Therefore, a low-cost carbonized bacterial cellulose material was prepared by direct calcination method, and used to remove multiple pesticides in tea infusions quickly and efficiently. CBC-350 has the best removal efficiency for 9 pesticides and then screened the best adsorption conditions. The adsorption isotherm experiment was carried out and indicated that the adsorption process was in consist with the Freundlich model. The thermodynamic parameters are also calculated. Moreover, the adsorption mechanism was discussed, which suggests that π-π interaction and hydrophobic action are the driving force during the adsorption process. Exhilaratingly, the CBC-350 also has excellent adsorption capacity compared to other adsorbents and can be reused at least five times.